SKRINING KADAR VITAMIN D SERUM PADA WANITA USIA SUBUR - Wahyuhidaya, Pratika; Wahyuntari, Evi; P, Oktavianus Wahyu (Universitas Muhammadiyah Mataram, 2025)
Abstract: WUS are women aged 15-49 years who are ready to face pregnancy. The services that can be provided in preparation for pregnancy include physical examinations, supporting examinations, nutritional supplementation and health consultation. One of the supporting examinations that can be provided is checking serum vitamin D levels which is associated with reproductive health problems such as infertility and also pregnancy complications such as preeclampsia. The research aims to examine serum vitamin D levels in WUS. This research was conducted on WUS who came to the RSKIA Sadewa Midwifery Polyclinic. The sampling technique used purposive sampling with a total of 40 respondents. Inclusion criteria: Women aged 20-35 years, want to have serum Vitamin D levels checked, female adolescents aged 13-18 years, registered. Exclusion criteria: Women of childbearing age who are pregnant. The results of screening for serum vitamin D levels in fertile women had found 28 (70%) respondents with infertility, 21 (52.5%) respondents with abnormal BMi and 27 (67.5%) respondents with vitamin D deficiency. countries with tropical climates, 67,5% of WUS experiences vitamin D deficiency and 52.5% infertility. The suggestion is that by getting an overview of Vitamin D levels in women of childbearing age, it can reduce complications in pregnancy.Abstrak: WUS merupakan Wanita usia 15-49 tahun yang siap menghadapai kehamilan. Adapun pelayanan yang dapat diberikan dalam persiapan kehamilan diantaranya pemeriksaan fisik, pemeriksaan penunjang, suplementasi gizi dan kosnultasi Kesehatan Pemeriksaan penunjang yang dapat diberikan salah satunya dengan pemeriksaan kadar vitamin D serum yang dikaitkan dengan salah satu masalah kesehatan reproduksi seperti infertilitas dan juga komplikasi kehamilan seperti preeklamsia. Penelitian bertujuan melakukan skrining kadar vitamin D serum pada WUS. Penelitian ini dilakukan pada WUS yang datang di poli Kebidanan RSKIA Sadewa. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah 40 responden. Kriteria inklusi: Wanita usia 20-35 tahun, bersedia dilakukan cek kadar serum Vitamin D, remaja putri usia 13- 18 tahun, tercatat. Kriteria eksklusi: Wanita usia subur yang sedang hamil. Hasil skrining kadar vitamin D serum pada wanita subur didapatkan 28 (70%) reponden dengan infertilitas, 21 (52,5%) responden dengan IMT tidak normal dan 27 (67,5%) responden dengan defisiensi vitamin D. Kesimpulan penelitian walaupun Indonesia sebagai negara dengan iklim tropis, 67,5% WUS mengalami defisiensi vitamin D dan 52,5% mengalami infertilitas. Saran dengan di dapatkan gambaran kadar Vitamin D pada wanita usia subur dapat mengurangi komplikasi pada kehamilan.